2023
DOI: 10.1007/s12187-022-10006-w
|View full text |Cite
|
Sign up to set email alerts
|

Digitally Deprived Children in Europe

Abstract: The COVID-19 pandemic has completely changed the need for internet connectivity and technological devices across the population, but especially among school-aged children. For a large proportion of pupils, access to a connected computer nowadays makes the difference between being able to keep up with their educational development and falling badly behind. This paper provides a detailed account of the digitally deprived children in Europe, according to the latest available wave of the European Union – Statistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…In families with low socio-economic status, low education levels, and especially Roma minority status (in the Romanian sample), offline vulnerabilities were reflected in children's accounts, who expressed that they struggle to keep up with their schoolmates. Gaps in access to DT, often presented in statistical data from Romania (Ayllón et al, 2020(Ayllón et al, , 2023, were also acknowledged by some of the interviewed children, who expected more support from their school in developing digital literacy to help them overcome their marginalisation. Regarding children's agency in relation to their family and social contexts, the in-depth analysis revealed that children have internal resources to strategies and adapt to a familial context that mediates their access to the digital world, which had already marked their young lives and might influence their future.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In families with low socio-economic status, low education levels, and especially Roma minority status (in the Romanian sample), offline vulnerabilities were reflected in children's accounts, who expressed that they struggle to keep up with their schoolmates. Gaps in access to DT, often presented in statistical data from Romania (Ayllón et al, 2020(Ayllón et al, , 2023, were also acknowledged by some of the interviewed children, who expected more support from their school in developing digital literacy to help them overcome their marginalisation. Regarding children's agency in relation to their family and social contexts, the in-depth analysis revealed that children have internal resources to strategies and adapt to a familial context that mediates their access to the digital world, which had already marked their young lives and might influence their future.…”
Section: Discussionmentioning
confidence: 93%
“…The parental capacity to negotiate and maintain boundaries could promote resilience among children and make them feel digitally competent. Still, in these cases, tutoring by educators would be necessary to avoid increasing existing digital divides (Ayllón et al, 2023). Although some interviewed children reported understanding and respecting family rules, other children reported that their parents were unaware of the programmes and platforms they used, allowing them to skirt the rules established for such activities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to avoid the overestimation or underestimation of teacher's own digital skills, it is necessary to cultivate a mentality of personal and professional growth both individually and collectively Promoting a reality-based mentality will lead to realistic solutions to educational problems, but also to the development of trust in teachers and other authorities who have influence in leading the socio-educational progress of a community Researchers concerned about the situation of the Romanian educational system conducted studies, prepared reports on the situation of access to ICT devices by students and teachers and of the teachers training to face the challenge of online teaching during the pandemic Some of them even recommended possible public policies in the Romanian education system (Ayllón et al, 2021;etc;Botnariuc, 2020;Florian & Țoc, 2020;IRES, 2020;Onete et al, 2020;Velicu, 2020Velicu, , 2021aVelicu, , 2021b Thus, in order for change to take place in the Romanian educational system, it is necessary for each of us (students, teachers, principals, etc) to be aware and accept when we have a problem and initiate its solution, practicing healthy relationships with responsible people and getting involved in the solution activities initiated by them The continuous struggle between subordinates and managers will only lead to inefficiency of activities and poor results of the educational system for which no one takes responsibility…”
Section: Discussionmentioning
confidence: 99%
“…has proliferated during the pandemic while raising concerns about personal data protection (e.g., the privacy of personal information, bank account details, and the use of human mobility tracking) and the quality of existing cybersecurity networks (Civil Security for Society, 2021−2022). Some significant measures have been introduced for cyber security (EU Cybersecurity Strategy-Horizon Europe, 2021−2027), 11 and digital literacy development programs have been implemented at the micro (Ayllón et al, 2021) and macro levels (European Commission, 2019−2024. 12 However, questions related to data access and data protection at the individual, household, and country levels remain challenging to answer due to the mobility restrictions imposed during lockdowns (Acquisti et al, 2020;Malgieri, 2020).…”
Section: Introductionmentioning
confidence: 99%